Comparison of different time-frequency analysis methods in estimating S2 split by tracking the instantaneous frequency [S2 Çiftleşmesinin Anlik Frekans Izlenmesi Yöntemiyle Kestiriminde Farkh Zaman-Frekans Yöntemlerinin Karşilaştirilmasi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
The second heart sound (S2) consists of aortic (A2) and pulmonary (P2) components which are produced by closures of aortic and pulmonary valves respectively for a healthy subject. There is a time split between these components namely S2 split which has very important diagnostic potential. There have been several methods proposed to measure the S2 split. Analyzing the signal in time- frequency domain is the most common and important phase of these proposed methods. In this work, we used and compared short time Fourier transform (STFT), continuous wavelet transform (CWT) and Wigner-Ville distribution (WVD) in estimating S2 split by tracking the instantaneous frequency (IF) of the S2 signal. Simulated data set were used in our comparisons. The best performance was achieved when WVD was used in estimating the IF. © 2015 IEEE.